2020
DOI: 10.3390/ijerph17176273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic and Anaerobic Fatigue Exercises on Postural Control and Recovery Time in Female Soccer Players

Abstract: Sixteen female soccer players (age = 20.19 ± 1.52 years; body mass = 56.52 ± 4.95 kg; body height = 164.81 ± 4.21 cm) with no history of lower extremity injury participated in the study. The Biodex SD Balance system was used to determine the non-dominant single-leg stability. In anaerobic exercise, each subject performed four maximal cycling efforts against a resistance equivalent to 0.075 kg/body mass for 30 s with three-minute rest intervals. In aerobic exercise, subjects performed the Bruce protocol on a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Indeed, postural sway assessed through CoP movements is highly variable, and coefficient of variation >10% is often observed ( Hébert-Losier and Murray, 2020 ). We used one repetition in our protocol because the fatigue could subside quickly after the completion of the fatiguing protocol ( Aboodarda et al, 2019 ; Güler et al, 2020 ). Nevertheless, more repetitions should be used prior to the fatiguing protocol to increase the rigor of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, postural sway assessed through CoP movements is highly variable, and coefficient of variation >10% is often observed ( Hébert-Losier and Murray, 2020 ). We used one repetition in our protocol because the fatigue could subside quickly after the completion of the fatiguing protocol ( Aboodarda et al, 2019 ; Güler et al, 2020 ). Nevertheless, more repetitions should be used prior to the fatiguing protocol to increase the rigor of the results.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increase in single-leg postural sway was produced by a zig-zag task in male and female athletes from field-based team sports (Lacey and Donne, 2019). Interestingly, aerobic fatigue had a more pronounced effect on single-leg postural sway than anaerobic fatigue in a study conducted on female soccer players (Güler et al, 2020). Recently, Bedo et al (2020) used a complex fatiguing protocol, consisting of multiple tasks, such as jumping, sidestep cutting, sprinting, and landing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recovery time may additionally depend on the tasks used to assess dynamic postural control and the loading protocol. Wright et al [ 20 ] and Güler et al [ 21 ] found lower recovery times of dynamic postural control measured with the Biodex Balance System after running and cycling. These different results might also be described with the different types of tasks used, challenging different types of dynamic postural control (reactive or anticipatory).…”
Section: Discussionmentioning
confidence: 99%
“…These studies were all using the Star Excursion Balance Test (SEBT) or the Y-Balance Test (YBT) to assess dynamic balance. Additionally, Wright et al [ 20 ] and Güler, Aras, Akça, Bianco, Lavanco, Paoli, and Şahin [ 21 ] found a negative effect of running and cycling on dynamic postural control measured with a Biodex Balance System. This load-induced decrease in dynamic postural control is supposed to be due to a loss of sensorimotor control and neuromuscular impairments [ 4 , 5 , 22 , 23 ] resulting from changes of the afferent information, altered proprioception, and changes of joint awareness and stability [ 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation